Ethnic, socioeconomic, and demographic determinants of generalized anxiety disorder and fear of COVID-19 among teenagers in California, United States: a cross-sectional analysis - Elina Kumra; Amit Patange (Frontiers in Education)
Background and objectiveThe COVID-19 pandemic substantially impacted mental health globally, leading to increased levels of anxiety and fear. Although it is well known that socioeconomic factors and ethnicity play a role in mental health outcomes, the intersectional effects of these determinants during the pandemic are unclear, especially among adolescents. Thus, this study sought to explore the relationship between socioeconomic factors, ethnicity, and two mental health parameters—fear of COVID-19 (FCV) and generalized anxiety disorder (GAD)—among high school students in California, United States.MethodsA cross-sectional analysis was performed with 990 high school-aged participants from the San Joaquin Valley and Santa Clara County, California, recruited via convenience/snowball sampling using an online questionnaire from 15 June to 14 August 2022. The Fear of Coronavirus Scale (FCV-19S) and Generalized Anxiety Disorder-7 (GAD-7) were used to measure fear and anxiety, respectively.ResultsThe results reveal significant associations between ethnicity, socioeconomic status (i.e., family income), and FCV-19S and GAD-7 scores. Severe GAD and FCV were reported in 9.8% (n = 97) and 8.38% (n = 83) of participants. Black participants reported significantly higher levels of FCV (F = 6.867, p < 0.001) and generalized anxiety (F = 17.066, <0.001) than their counterparts Additionally, girls exhibited higher anxiety scores (t = 2.960, p = 0.003, CI = 0.23–1.15) and fear scores (t = 3.619, p = 0.001, CI = 0.40–1.37) than boys. Furthermore, fear and anxiety scores exhibited a strong positive correlation (r = 0.702, p < 0.001).ConclusionThis study suggests that gender, ethnicity, and socioeconomic factors are significantly linked to higher levels of FCV and GAD in teenagers during the pandemic. These findings underscore the importance of considering social determinants of mental health when addressing the psychological impact of COVID-19 on teenagers, particularly for vulnerable populations.